ORGANIZACIÓN CONTABLE AL ALMACEN AGROPECUARIO ¨AGROCELÍN¨ DE LA CIUDAD DE LOJA, DURANTE EL PERÍODO ENERO – MARZO del 2016 - Guamán Vera, Maritza del Cisne (2017)
As a graduate of the Accounting and Auditing Career, Juridical, Social and Administrative Faculty of the National University of Loja, and committed to legal, social and administrative development; there is a need to carry out a study of our socioeconomic environment. Therefore, I have proposed the development of this thesis research project entitled: "ACCOUNTING ORGANIZATION TO THE AGRICULTURAL WAREHOUSE" AGROPELLI "OF THE CITY OF SHOP, DURING THE PERIOD JANUARY - MARCH OF 2016, fulfilling the specific objectives such as: To make a plan and manual of accounts according to the needs of the company, the accounting accounts were established with their respective codification and description allowing ordering them and identifying them during the accounting process. Carrying out the initial inventory to determine the rights and obligations owned by the company, the physical verification of all the assets of the company was carried out, thus determining the initial inventory as the basis for the preparation of the initial situation. To design the auxiliary records of sales, purchases, payment roles and provisions, ancillary records were elaborated with the purpose of simplifying the movement of operations. Prepare the accounting process through the system of permanent inventory control, until obtaining the financial statements. A memorandum was made of the operations being supported by the source documentation, expediting the registration in the journal, 5 major, checking balance, worksheet with their respective adjustments until concluding with obtaining the financial statements that reflect the economic situation and of the company. It is established that when implementing the accounting organization for the "AGROCELÍN" Agricultural Warehouse, it was possible to adapt a relevant treatment of the accounting information once in investigating, it was determined the ignorance of the real economic and financial situation of the company, interested parties of the economic activity know in detail the operation of the same, therefore it is considered necessary the emergent application of this proposal, with the purpose of reaching the expectations that the company keeps on going to correct the shortcomings to intervene immediately avoiding any future adversity, and fortify the economic performance in favor of business growth and improvement in response to its competitive environment.